2024
DOI: 10.1021/acs.est.3c07147
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Settling Velocity of Biofilm-Encrusted Microplastics: Accounting for Biofilms as an Equivalent to Surface Roughness

Daizong Meng,
Yuzhu Li

Abstract: While it is well established that a biofilm contributes to the sinking of plastics, the underlying mechanisms of how it influences the vertical transport of plastics have not been well explained. In this context, our study dives into the intricate effects of biofouling on the settling velocity (W s ) of microplastics (MPs) within the fluid. We adopt the perspective that the biofilm is a form of surface roughness impacting the drag coefficient (C d ) and vertical settling of MPs. By advancing the biofouling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that the biofilm on the surface of microplastics can be used as a kind of surface roughness, and the sedimentation rate can be changed by changing the resistance coefficient of microplastics during the sedimentation process. It has also been pointed out that the multilayer structure and anisotropy of microbial biofilms are not exactly equivalent to the roughness of traditional particles [159]. The spectral absorption summit of the functional groups of PE plastics was exposed to seawater changes, producing an additional peak at 1700, which is believed to be mainly due to the C==O produced by the decomposition of microplastics [156].…”
Section: Water Microorganismsmentioning
confidence: 99%
“…Recent studies have shown that the biofilm on the surface of microplastics can be used as a kind of surface roughness, and the sedimentation rate can be changed by changing the resistance coefficient of microplastics during the sedimentation process. It has also been pointed out that the multilayer structure and anisotropy of microbial biofilms are not exactly equivalent to the roughness of traditional particles [159]. The spectral absorption summit of the functional groups of PE plastics was exposed to seawater changes, producing an additional peak at 1700, which is believed to be mainly due to the C==O produced by the decomposition of microplastics [156].…”
Section: Water Microorganismsmentioning
confidence: 99%